2006
DOI: 10.1111/j.1651-2227.2006.tb02197.x
|View full text |Cite
|
Sign up to set email alerts
|

The true cause of pyloric stenosis is hyperacidity

Abstract: Persisting duodenal hyperacidity is created by an inherited high PCM and loss of gastrin control. These two factors produce pyloric stenosis through work hypertrophy from repeated pyloric contraction in response to hyperacidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…The pathogenesis of IHPS is multifactorial and includes hypergastrinemia, abnormal pyloric innervation, genetic mutations, and environmental influences [5] [14]. This study was performed in Nordrhein-Westfalen (NRW).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of IHPS is multifactorial and includes hypergastrinemia, abnormal pyloric innervation, genetic mutations, and environmental influences [5] [14]. This study was performed in Nordrhein-Westfalen (NRW).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of the pylorus tumor remains enigmatic. There is good evidence that the inherited hyperacidity caused by an immature feedback mechanism in gastric production is the predominant factor [5]. However, whether the elevation of serum gastrin is a primary or secondary phenomenon remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to macrolides has been linked and is considered a possible risk factor in the development of HPS [76]. Other researchers have suggested that growth factors, such as hormones and peptides [77,78], or gastric acid hypersecretion may play a role [79].…”
Section: Hypertrophic Pyloric Stenosis Pathophysiologymentioning
confidence: 99%
“…IHPS are the common leading etiology for the nonbilious emesis requiring a pediatric surgical intervention [6]. The peak age of presentation in an infant is between 3 to 6 weeks of age [7]. Reports also have described early and late presentation of 2 to 8 weeks of age, respectively.…”
Section: Introductionmentioning
confidence: 99%